Multicultural Families and Creative Children. (September 2014) - Chang, Jen-Ho; Hsu, Chin-Chun; Shih, Nai-Hua; Chen, Hsueh-Chih
The link between multicultural experience and creativity is consistently supported by many empirical studies. However, most of these results are limited to adult participants with foreign living experience. The present study extended previous studies and investigated the positive relationship between multicultural experience and creativity in Taiwan young adolescents living in binational families. With more than 700 young adolescents, the results showed that young adolescents from binational families had parents with lower socioeconomic status than monocultural families. However, young adolescents from binational families performed better on creativity tests (fluency, flexibility, and originality) than those from monocultural families. In addition, when variables of family background and young adolescents' personalities were controlled for, the effect of binational families on creativity remained. The implications for research on multicultural families and young adolescents' creative performance are discussed.